PROSPECTS OF BIOETHANOL AND PELLET PRODUCTION BASED ON SWEET SORGHUM CULTIVARS GROWING ON RECLAIMED LANDS - Kharytonov , М.; Бабенко, М.; Rula, І.; Lemishko , С.; Martynova, Н.; Hamandii, В. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
Field experiments on the growing of Ukrainian and American cultivars of sugar sorghum were conducted in the conditions of the steppe zone of Ukraine at the Pokrov educational and research station of land reclamation. The station was founded almost 50 years ago on a 60 m high dump after mining and technical reclamation works related to the open pit quarry of manganese ore. Three sweet sorghum hybrids of Ukrainian selection including Medove, Zubr, Pokrovske, one variety called Silosne – 42, and four American hybrids (SS506, Sioux, Mohawk, G1990) were studied in the field conditions in 2017–2018. A two-factor field experiment was launched, namely Factor A – sweet sorghum hybrids of domestic and American origin; factor B – two types of soil (chernozem mass and phytomeliorated loess-like loam). The main goal of the study was to assess prospects for production of high-quality biological raw material after sweet sorghum cultivars growing on reclaimed lands. Plants grown on chernozem had little higher Brix values than those on loess loam. The theoretical yield of ethanol of the high-yield hybrids (Zubr, Medove, Mohawk, SS506) was 2500–3600 l ha-1, and of the low-yield hybrids (Sioux and Silosne-42) – 705–1600 l ha-1. The study of biomass thermolysis processes of the Ukrainian and American cultivars of sweet sorghum revealed both similarities and differences in three indicators (mass loss, speed of decomposition processes, thermal effect). Chemical reactions of destruction of the samples of the Ukrainian cultivars were characterized by a greater release of energy than destruction of the samples of the American hybrids. There was almost no difference in the nature of mass loss within hybrid groups on the black soil. In the samples of the Ukrainian cultivars, the rate of mass loss increased at earlier stages at temperatures of 170–175 oC, while the samples of the American hybrids began to rapidly lose the mass only at temperatures of 230–240 oC. The duration of thermolysis on chernozem was longer than on loess like loam and was 40–50 °C – 550–580 °C in the Ukrainian cultivars and 50–60 °C – 550–590 °C in the American hybrids. Therefore, the obtained results of the evaluation of the theoretical yield of ethanol and processes of thermolysis of bagasse made it possible to identify some American and Ukrainian cultivars for growing on the two types of reclaimed land.